Larvicidal Potential of Crude Methanolic Leaf Extract of Azadirachta Indica On Mosquito Larvae - Timothy Chombo (Student's Journal of Health Research, 2021)
Background Mosquitoes are pestiferous vectors responsible for the transmission of various dreadful diseases like malaria and yellow fever, causing millions of deaths every year. Indiscriminate use of chemical insecticides has resulted in the development of resistance by these organisms, resulting in rebounding vectorial capacity. Traditional Ugandan system of medicine mentions neem (Azadirachta Indica) to have many medicinal properties. The present study has assess the larvicidal ability of the aqueous extracts of ten medicinal plants against mosquito larvae. Method  Six third and fourth instar larvae, each were introduced into treatment trays containing 15 ml of their natural growth medium. To the treatment set, respective concentrations of the plant extracts (0.4, 0.8, 1.2, 1.6 ml) were added from the stock solution; maintaining a relative concentration of the plant extract as 2, 4, 6, 8mg/ml respectively. A control was maintained, containing only larvae and natural growth medium. Mortality counts of larvae were monitored at regular intervals i.e. 6, 12, and 24Hours after treatment. Larvae were considered dead if they settle and remain motionless in the bottom of the test beaker with no response to light or mechanical stimulus or not recovering life functions even after being transferred to their growth medium. Results  It was found that the crude methanolic neem leaf extract showed significant larvicidal effect at different concentrations, hence can be safely used as a potent larvicidal agent. LC50=3.02mg/ml LD90=33.11mg/ml. There are strong correlation between mortalities observed in larvae and extract concentration Conclusion                                                           The leaf extract of Azadirachta Indica is highly toxic even at low doses this plant may eventually prove to be a useful larvicide. Further analysis is required to isolate the active principles and optimum dosages, responsible for larvicidal activity.